Pengaruh Lembaga Pendidikan Islam Deep Learning Kurikulum Berbasis Cinta Pengembangan Materi Ajar pada Sekolah Dasar: The Influence of Deep Learning Islamic Education Institutions, Love-Based Curriculum on the Development of Teaching Materials in Elementary Schools - Nabila Rahma Daniah; Imam Sujadmiko; Ahmad Zainuri; Frika Fatimah Zahra (TARBIYAH: Jurnal Pendidikan dan Pembelajaran, 2025)
This study aims to examine the impact of Islamic educational institutions, the deep learning approach, and a curriculum based on love on the development of teaching materials in elementary schools. Islamic education plays a foundational role in shaping students' character through the internalization of religious, moral, and social values. However, current learning practices in many elementary schools still focus mainly on textual materials and have not fully addressed the holistic development of students. The concept of a love-based curriculum is seen as an innovative approach that emphasizes love, empathy, and role modeling, which can create a more humane and meaningful learning environment. Meanwhile, deep learning contributes to enhancing students' critical thinking, collaborative, and contextual skills. This research uses a literature study method by analyzing relevant primary and secondary sources on Islamic education, deep learning, love-based curriculum, and the development of teaching materials. The findings show that integrating these three aspects has strategic potential in creating deeper, more holistic, and student-centered learning experiences that meet the developmental needs of children, while also strengthening their character and spirituality in elementary schools.